2022
DOI: 10.3390/app122211361
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and Odour Qualities of Alkylpyrazines Occurring in Chocolate and Cocoa Products

Abstract: A total of 40 pyrazine compounds of cocoa and chocolate were discovered through a literature analysis. Data on the alkylpyrazines’ antibacterial properties were gathered. It was discovered that 12 substances were effective against bacteria, fungus and oomycetes. Following calculations using PASS and AntiBac-Pred, 15 substances were identified as potentially having the ability to inhibit the growth of the Picornavirus, Yersinia pestis, Resistant Mycobacterium tuberculosis, Mycobacterium bovis BCG (Bacillus Calm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…viz., D-Pinitol obtained from carob tree are known to have antidiabetic, anticancer, antioxidant and anti-inflammatory activity (Azab, 2022), Benzoic acid are known to counteract pathogen related damage and yield loss in lettuce plants thereby acting as antimicrobial agent (Windisch et al, 2021), 17hydroxylinolenic acid are found to have anti-inflammatory activity in mammalian cells (Kolar et al, 2019), 2-Methylbenzaldehyde obtained from Cymbopogon martini essential oil has been reported to exhibit antioxidant, antibacterial and antifungal activities (Soorya et al, 2013), L-Onithine and Trans-zeatin are known to have immunological potential (Mika et al, 2014;Hallmark, 2020), 5,6,7,8-Tetrahydro-2,4-dimethylquinoline are known to have antitumor, antimicrobial, antiviral and immunoregulatory effects (Saurabhi et al, 2020), 2,4-Dihydroxy benzoic acid, 9,10, Dihydroxy-12-13-epoxyoctadecanoate and Citronelloglucoside are reported to have antioxidant, anticancer, antimicrobial, antidiabetic activity (Azab, 2022;Zhenjiang 2019;Ashwini, 2015;Santos, 2019) repectively. (R)-(+)-2 Pyrrolidone-5-carboxylic acid, 2,3-Dihydro-6-methyl-1-5-propanoyl-1Hpyrrolizine and 3,5-Dimethyl-2-propylpyrazine are known to have antimicrobial activity (Yang et al, 1997;Moreira et al, 2018;Cherniienko et al, 2022), 2,3-Dihydro-6-methyl-1-5-propanoyl- 1H-pyrrolizine are also known to have anti-inflammatory potentials besides Indoleacrylic acid (Wlodarska et al, 2017), O-Desmethylquinine are known to have antimalarial, antipyretic activity (Adnyana et al, 2013), 2 S-hydroxyoctadecanoic acid are known for antiallergic activity (Korinek, 2017), Gentisic acid for antidiabetic activity (Mechchate, 2021), Coiine reported to have antinociceptive effect (Arihan et al, 2009), Stovaine is used as local anesthesia (Wlodarska et al, 2017), Procaine is reported to have analgesic potential (Outland and Hanlon, 1940), Glutamylisoleucine in used as a potential biomarker of prostate cancer (Thacker, 2021) and Fabianine isolated from Aerva sanguinolenta (L). Blume are known to have antioxidant and antidiabetic properties (Sarkar, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…viz., D-Pinitol obtained from carob tree are known to have antidiabetic, anticancer, antioxidant and anti-inflammatory activity (Azab, 2022), Benzoic acid are known to counteract pathogen related damage and yield loss in lettuce plants thereby acting as antimicrobial agent (Windisch et al, 2021), 17hydroxylinolenic acid are found to have anti-inflammatory activity in mammalian cells (Kolar et al, 2019), 2-Methylbenzaldehyde obtained from Cymbopogon martini essential oil has been reported to exhibit antioxidant, antibacterial and antifungal activities (Soorya et al, 2013), L-Onithine and Trans-zeatin are known to have immunological potential (Mika et al, 2014;Hallmark, 2020), 5,6,7,8-Tetrahydro-2,4-dimethylquinoline are known to have antitumor, antimicrobial, antiviral and immunoregulatory effects (Saurabhi et al, 2020), 2,4-Dihydroxy benzoic acid, 9,10, Dihydroxy-12-13-epoxyoctadecanoate and Citronelloglucoside are reported to have antioxidant, anticancer, antimicrobial, antidiabetic activity (Azab, 2022;Zhenjiang 2019;Ashwini, 2015;Santos, 2019) repectively. (R)-(+)-2 Pyrrolidone-5-carboxylic acid, 2,3-Dihydro-6-methyl-1-5-propanoyl-1Hpyrrolizine and 3,5-Dimethyl-2-propylpyrazine are known to have antimicrobial activity (Yang et al, 1997;Moreira et al, 2018;Cherniienko et al, 2022), 2,3-Dihydro-6-methyl-1-5-propanoyl- 1H-pyrrolizine are also known to have anti-inflammatory potentials besides Indoleacrylic acid (Wlodarska et al, 2017), O-Desmethylquinine are known to have antimalarial, antipyretic activity (Adnyana et al, 2013), 2 S-hydroxyoctadecanoic acid are known for antiallergic activity (Korinek, 2017), Gentisic acid for antidiabetic activity (Mechchate, 2021), Coiine reported to have antinociceptive effect (Arihan et al, 2009), Stovaine is used as local anesthesia (Wlodarska et al, 2017), Procaine is reported to have analgesic potential (Outland and Hanlon, 1940), Glutamylisoleucine in used as a potential biomarker of prostate cancer (Thacker, 2021) and Fabianine isolated from Aerva sanguinolenta (L). Blume are known to have antioxidant and antidiabetic properties (Sarkar, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…On the above analysis, this study used TOPSIS to analyze the importance of 57 characteristic volatile compounds in the process of distinguishing MD from PD and found that (Figure 2E), only 8 characteristic volatile compounds had a weight of 10% or more, namely methyl salicylate (61.32%), (E)-3-hexen-1-ol acetate (49.79%), (Z)-3-hexen-1-ol acetate (49.79%), 1,6-dihydrocarveol (17.27%), gamma-terpineol (17.27%), dihydromyrcenol (16.16%), linalyl acetate (13.80%), and 2-isobutylpyrazine (10.93%). Of eight characteristic volatile compounds that are considered essential to odor characteristics of tea, methyl salicylate, (E)-3-hexen-1-ol acetate, (Z)-3-hexen-1-ol acetate, and 2-isobutylpyrazine mainly have a fruity odor characteristic [20][21][22][23], dihydromyrcenol has a floral odor characteristic [24], 1,6-dihydrocarveol has a green odor characteristic [25], and gamma-terpineol and linalyl acetate have a woody odor characteristic [26,27]. It can be seen that MD and PD differed mainly in fruity, floral, green, and woody odor characteristics, while the difference in the content of volatile compounds of different odor characteristics may lead to the difference in the intensity of different odor characteristics between MD and PD.…”
Section: Screening For Characteristic Volatile Compounds and Their Od...mentioning
confidence: 99%
“…This review article cited data for 48 types of compounds known from the previous, scattered literature information on this topic. The earlier mentioned pyrazine system also appeared in the concept paper of Cherniienko et al [7], in which, based on a review of the literature data, an attempt was made to correlate the odor properties and the antibacterial ability of 40 pyrazine derivatives found in cocoa and chocolate and responsible for their specific smells. The antimicrobial properties of these compounds have been calculated for various types of microorganisms using widespread computational prediction programs.…”
mentioning
confidence: 94%